Improving Student Understanding Through the Development of Teaching Curriculum Textbooks for Madrasah Ibtidaiyah Teacher Education Learning Curriculum - Nuzulia, Nuril (Universitas Muhammadiyah Sidoarjo, 2023)
Development of Learning Curriculum Textbooks to Increase Madrasah Ibtidaiyah Teacher Education Students' Understanding of Learning Curriculum subjects at UIN Maulana Malik Ibrahim Malang is one of the means to help students understand and improve pedagogical abilities. The need to provide interesting and creative learning media in a lesson that aims to increase students' understanding and grades is one of the reasons behind this development research. This research and development method uses research and development (R&D) research. The procedure for developing this research uses a model, namely the Borg and Gall model. This research was conducted at the Madrasah Ibtidaiyah Teacher Education Study Program. Data collection techniques in this study were tests and observations. The data obtained were analyzed quantitatively and qualitatively. The development results were a book,